Obesity and periodontal disease - Jagannathachary Sunitha; Kamaraj Dinesh (Wolters Kluwer Medknow Publications, 2010)
Obesity is characterized by the abnormal or excessive deposition of fat in the adipose tissue. Its consequences go far beyond adverse metabolic effects on health, causing an increase in oxidative stress, which leads not only to endothelial dysfunction but also to negative effects in relation to periodontitis, because of the increase in proinflammatory cytokines. Thus obesity appears to participate in the multifactorial phenomenon of causality of periodontitis through the increased production of reactive oxygen species. The possible causal relationship between obesity and periodontitis and potential underlying biological mechanisms remain to be established; however, the adipose tissue actively secretes a variety of cytokines and hormones that are involved in inflammatory processes, pointing toward similar pathways involved in the pathophysiology of obesity, periodontitis and related inflammatory diseases. So the aim of this article is to get an overview of the association between obesity and periodontitis and to review adipose-tissue - derived hormones and cytokines that are involved in inflammatory processes and their relationship to periodontitis.